2012
DOI: 10.3233/jad-2011-110554
|View full text |Cite
|
Sign up to set email alerts
|

Association of Apolipoprotein E ε4 (ApoE ε4) Homozygosity with Psychiatric Behavioral Symptoms

Abstract: To examine the relationship between apolipoprotein E ε4 (ApoE ε4) and psychiatric symptoms, we compared ε4/ε4, ε3/ε3, and ε3/ε4 subjects. 659 outpatients with memory complaints underwent comprehensive neuropsychiatric assessment interview and neurological examination and ApoE genotyping: 98 were ε4/ε4. 18.4% (n = 18) ε4/ε4, 19.3% (n = 45) ε3/ε4, and 5.4% (n = 14) ε3/ε3 presented with symptoms of anxiety (p = 0.00001). ε4/ε4 patients with mild cognitive impairment (MCI; p < 0.0001) and those with Alzheimer's di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 25 publications
0
9
1
Order By: Relevance
“…Regardless, in a study of over 1800 patients with MCI, baseline levels of depression were associated with increased incidence of dementia and AD. [48] Neuropsychiatric symptoms and poor psychological well-being are also associated with Alzheimer's disease pathology, including cerebral amyloid deposition [49,50], APOE Ɛ4 [51,52], and Alzheimer's cerebrospinal fluid markers. [53] Targeting neuropsychiatric symptoms in adults with MCI may delay the transition to dementia, [54] a key treatment focus at this time given limited treatment options to prevent progression.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, in a study of over 1800 patients with MCI, baseline levels of depression were associated with increased incidence of dementia and AD. [48] Neuropsychiatric symptoms and poor psychological well-being are also associated with Alzheimer's disease pathology, including cerebral amyloid deposition [49,50], APOE Ɛ4 [51,52], and Alzheimer's cerebrospinal fluid markers. [53] Targeting neuropsychiatric symptoms in adults with MCI may delay the transition to dementia, [54] a key treatment focus at this time given limited treatment options to prevent progression.…”
Section: Discussionmentioning
confidence: 99%
“…The Val66Met polymorphism of BDNF gene is associated with decreased secretion of BDNF and has been implicated as a possible risk allele for anxiety [41] and worse cognitive functioning [42]. The Apolipoprotein E ε4 variant is the largest known genetic risk for Alzheimer’s disease and also has been implicated with anxiety [43] and stress [44]. Likewise genes associated with serotonin reuptake and the dopaminergic systems have been implicated with anxiety and cognitive performance [4547].…”
Section: Discussionmentioning
confidence: 99%
“…23 There may be differences in neuropsychiatric symptoms observed in patients who are homozygous for the APOE E4 allele as opposed to heterozygous. Michels et al 24 found that patients who were homozygous for the APOE E4 allele had the highest rates of anxiety, higher rates of depression than those who did not carry the E4 allele, and higher rates of hallucinations than those who were either heterozygous or did not carry the allele. Van der Flier et al 25 also noted that there may be a dose effect of the E4 allele, finding that those patients who were homozygous for the E4 allele were more likely to have delusions and agitation/aggression.…”
Section: Relationship Of Neuropsychiatric Symptoms and Apoe E4 Statusmentioning
confidence: 99%